Nature and Origin of Anorthositic Suites - Emslie, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary Anorthositic suites are spatially and temporally associated assemblages of rocks ranging from gabbro, troctolite and anorthosite through diorite to granitic compositions. The largest known concentration of these rocks in the world is in the Grenville Province and in Labrador north of the Grenville Front. New data on the rock and mineral chemistry of the suites are leading to reassessment of ideas about their origins. One of the keys to understanding the tectonic evolution of the Grenville Province lies in correct interpretation of anorthosite suites in terms of the igneous processes that formed them and their subsequent metamorphism. Renewed appraisal of the economic potential of anorthositic suites is taking place on several fronts.